Neuronal Alterations and Antioxidant Status of Lipopolysaccharide Induced Neuronal damage in Mice: Efficacy of Three Medicinal Plants - B. P. Olatunji, T. R. Fasola, S. A. Onasanwo, A. J. Akinyemi, P. A. Adeniyi, A. O. Ishola (Journal of Applied Pharmaceutical Science, 2017)
Background: Several factors including neuroinflammation and oxidative stress formation contribute to the progression and development of cognitive impairment. Lipopolysaccharide (LPS) injection has been used as non-transgenic mouse models for Alzheimer’s diseases (AD). Plant medicine has been proposed to be the prospect in treatment/ management of neurodegenerative disease. Aim: The present study sought to evaluate the effect of three medicinal plants (Bacopa floribunda (R.Br)Wettst, Scoparia dulcis L and Cordia millenii Bak.) locally used for memory enhancement on neuronal histology and antioxidant status against Lipopolysaccharide induced neuronal damage in mice. Methods: Forty-nine (49) BALB/c male mice were randomly grouped into seven (7) groups of 7 mice each. All animals except in group I control (vehicle), were injected intraperitoneally (I.P.) with LPS (250 μg/kg) once, after oral pre-treatment with plant extracts and control drugs for 7 days. Group II (untreated) received LPS only (250 μg/kg) , group III received LPS + Sulindac Sulfide (SS, 4 mg/kg), group IV received LPS + Donepezil (DPZ, 1 mg/kg) group V, VI, and VII received LPS + 200 mg/kg of plant extracts [Scoparia dulcis (SD), Bacopa floribunda (BF), and Cordia millenii (CM)] respectively. After the experiment, histological analysis of the hippocampus from the whole brain was carried out while the other brain tissues comprising frontal cortex and cerebellum were used for determination of biomarkers of antioxidant status such as catalase (CAT); superoxide dismutase (SOD); malondialdehyde (MDA) and reduced glutathione (GSH). Results: Oral administration of LPS induced neuronal damage through cell death as evidenced by the histological analysis and altered brain antioxidant status in mice. However, the plant extracts were able to prevent such neuronal alterations and restored the antioxidant status when compared to the LPS induced neuronal damage in mice. Conclusion: LPS induced neuroinflammation was prevented by the extracts of; B. floribunda, S. dulcis and C. millenni. Neural damage was also prevented by the extracts. This activity could be attributed to their antioxidant potential as evidenced from their inhibitory effect on MDA and increased CAT activity and GSH. Nevertheless, other possible mechanisms of action against neuronal damage need to be assessed to further justify their use traditionally in the treatment/management of neurodegenerative diseases.
Keywords: Neuroinflammation, Scoparia dulcis, Bacopa floribunda, Cordia millenii, Lipopolysaccharide.